Argument Types and Fallacies in Legal Argumentation - Bustamante, Thomas (Springer, 2016)
This book provides theoretical tools for evaluating the soundness of arguments in the context of legal argumentation. It deals with a number of general argument types and their particular use in legal argumentation. It provides detailed analyses of argument from authority, argument ad hominem, argument from ignorance, slippery slope argument and other general argument types. Each of these argument types can be used to construct arguments that are sound as well as arguments that are unsound. To evaluate an argument correctly one must be able to distinguish the sound instances of a certain argument type from its unsound instances. This book promotes the development of theoretical tools for this task.